Nanofiber-based systems intended for diabetes - Hassan Maleki; Kamyar Khoshnevisan; Sayed Mahmoud Sajjadi-Jazi; Hadi Baharifar; Maryam Doostan; Nazanin Khoshnevisan; Farshad Sharifi (Journal of Nanobiotechnology, 2021)
Abstract Diabetic mellitus (DM) is the most communal metabolic disease resulting from a defect in insulin secretion, causing hyperglycemia by promoting the progressive destruction of pancreatic β cells. This autoimmune disease causes many severe disorders leading to organ failure, lower extremity amputations, and ultimately death. Modern delivery systems e.g., nanofiber (NF)-based systems fabricated by natural and synthetic or both materials to deliver therapeutics agents and cells, could be the harbinger of a new era to obviate DM complications. Such delivery systems can effectively deliver macromolecules (insulin) and small molecules. Besides, NF scaffolds can provide an ideal microenvironment to cell therapy for pancreatic β cell transplantation and pancreatic tissue engineering. Numerous studies indicated the potential usage of therapeutics/cells-incorporated NF mats to proliferate/regenerate/remodeling the structural and functional properties of diabetic skin ulcers. Thus, we intended to discuss the aforementioned features of the NF system for DM complications in detail. Graphic abstract